A formação continuada para docentes no discurso dos organismos internacionais - Rodrigues, Leticia Moraes [UNIFESP] (2020)
This research deals with continuing education for teachers and had the general objective of identifying and discussing the recommendations and prescriptions present in documents from international organizations for teacher education, with emphasis on continuing education in the "in service" modality. As an unfolding of the general objective, the identification and discussion about the context of production of the speeches of international organizations regarding continuing education were established as specific objectives, as well as the verification of the existence of a pattern that guides the conceptions about such a formation process by international organizations. The hypothesis that guided the investigation was that there is a model of continuing education for teachers, defended by international organizations, that prescribe content and form for such actions and that, not always, meets the demands of teacher training with a view to improving the pedagogical practice. In order to carry out the investigation, we carried out the analysis of documents from the World Bank (BM), the Organization for Economic Cooperation and Development (OECD) and the United Nations Organization for Education, Science and Culture (UNESCO), identifying and discussing recommendations and / or prescriptions for teacher training, especially for teachers in office. As a theoretical reference, the Political Cycle approach was used (BOWE, BALL and GOLD, 1992) and, thus, the concept of context of influence in the scope of documentary analysis. We also count on the contributions Bardin (1977) with his concept of organization of analysis, of Azanha (1992), with the concept of pedagogical abstractionism and of Scheffler (1974), with the concept of slogans. The results of our study corroborate the hypothesis raised that there is a training model, prescribed by the international organizations analyzed. It was also possible for us to identify a strong tendency to put continuing training in opposition to initial training, making the former a correction tool. what organisms perceive to be mistakes in initial training; in this sense, we found through documentary analysis the existence of a discursive pattern, present in the documents of the international organizations analyzed, which deal with continuing education, carried out throughout the professional teaching practice, as an efficient way to align school content with the requirements of a global economy, valuing the “codes of modernity”, with a view to a more dynamic, flexible, productive, competitive and efficient market.